Concurrent magneto-optical imaging and magneto-transport readout of electrical switching of insulating antiferromagnetic thin films - Schreiber, F.; Baldrati, L.; Schmitt, Christin; Ramos, Rafael; Saitoh, Eiji; Lebrun, Romain; Klaeui, M. (Applied Physics Letters, 2020)
We demonstrate stable and reversible current induced switching of large-area (>100 μm2) antiferromagnetic domains in NiO/Pt by performing concurrent transport and magneto-optical imaging measurements in an adapted Kerr microscope. By correlating the magnetic images of the antiferromagnetic domain changes and magneto-transport signal response in these current-induced switching experiments, we disentangle magnetic and non-magnetic contributions to the transport signal. Our table-top approach establishes a robust procedure to subtract the non-magnetic contributions in the transport signal and extract the spin-Hall magnetoresistance response associated with the switching of the antiferromagnetic domains, enabling one to deduce details of the antiferromagnetic switching from simple transport measurements.
CRIS-Team Scopus Importer:2023-03-27